Synthesis and T-type calcium channel-blocking effects of aryl(1,5-disubstituted-pyrazol-3-yl)methyl sulfonamides for neuropathic pain treatment - Kim, Jung Hyun; Keum, Gyochang; Chung, Hesson; Nam, Ghilsoo (ELSEVIER FRANCE-EDITIONS SCIENTIFIQUES MEDICALES ELSEVIER, 2016)
A novel series of aryl(1,5-disubstituted pyrazol-3-yl)methyl sulfonamide derivatives was designed, synthesized, and evaluated for T-type calcium channel (ctiG and chm) inhibitory activity. We identified several compounds, 9a, 9b, 9g, and 9h that displayed good T-type channel inhibitory potency with low hERG channel and CYP450 inhibition. Among them, 9a and 9b exhibited neuropathic pain alleviation effects in mechanical and cold allodynia induced in the SNL rat model. Compounds 9a and 9b displayed better efficacy than mibefradil and gabapentin against cold allodynia. In particular, compound 9a seemed to be valuable as shown fast acting performance in mechanical neuropathic pain model. (C) 2016 Elsevier Masson SAS. All rights reserved'.
Keywords: CA2+ CHANNELS; PERIPHERAL NEUROPATHY; RAT; MODEL; ZONISAMIDE; ALLODYNIA; BLOCKERS; NEURONS